Penerapan Model Problem Based Learning Bebantuan Media Pakapati untuk Meningkatkan Hasil Belajar - Mohamad Amhar; Rohandi Rohandi; Monica Chandra Wahyu (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2023)
The research background is the low student learning outcomes in mathematics, especially in cube root material. This type of research is classroom action research (CAR) which aims to investigate the application of the Problem Based Learning (PBL) model with the help of Pakapati media in improving student learning outcomes. The PBL method is used as a learning approach that emphasizes problem solving and developing critical thinking skills, while Pakapati media is used as an interactive tool to support active learning. This research was conducted through two cycles of CAR. The research subjects were fifth grade students at Kanisius Gayam I Elementary School Yogyakarta, which consisted of 30 students. Data collection was carried out by interviews, observations and tests. Data analysis techniques used are quantitative and qualitative. The results of the study show that the application of the PBL model with the help of Pakapati media can improve student learning outcomes. This can be shown from the increase in student learning outcomes starting from the pre-cycle stage to cycle 2 where in the pre-cycle the percentage of students who achieve scores above the Minimum Completeness Criteria (KKM) is 30%, in cycle I it becomes 40%, and 60% in cycle II.